Riots and the Window of Opportunity for Coup Plotters: Evidence on the Link between Urban Protests and Coups d'État - Lena Gerling (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper investigates the impact of urban protests on coup attempts in a sample of 39 SSA countries for the period 1990 to 2007. Widespread public discontent, especially when occurring in urban centers, can act as a trigger of coups in autocratic regimes by opening a window of opportunity for leadership removals. Variation in rainfall is used to create an instrument for protests. The results show that rainfall-related popular uprisings in urban areas increase the likelihood of a coup attempt.
Keywords: C26; D74; P16; 330